Genome-wide association analysis in dilated cardiomyopathy reveals two new players in systolic heart failure on chromosomes 3p25.1 and 22q11.23. (3rd March 2021) - Garnier, Sophie; Harakalova, Magdalena; Weiss, Stefan; Mokry, Michal; Regitz-Zagrosek, Vera; Hengstenberg, Christian; Cappola, Thomas P; Isnard, Richard; Arbustini, Eloisa; Cook, Stuart A; van Setten, Jessica; Calis, Jorg J A; et al.
Abstract: Aims : Our objective was to better understand the genetic bases of dilated cardiomyopathy (DCM), a leading cause of systolic heart failure. Methods and results : We conducted the largest genome-wide association study performed so far in DCM, with 2719 cases and 4440 controls in the discovery population. We identified and replicated two new DCM-associated loci on chromosome 3p25.1 [lead single-nucleotide polymorphism (SNP) rs62232870, P = 8.7 × 10 −11 and 7.7 × 10 −4 in the discovery and replication steps, respectively] and chromosome 22q11.23 (lead SNP rs7284877, P = 3.3 × 10 −8 and 1.4 × 10 −3 in the discovery and replication steps, respectively), while confirming two previously identified DCM loci on chromosomes 10 and 1, BAG3 and HSPB7 . A genetic risk score constructed from the number of risk alleles at these four DCM loci revealed a 3-fold increased risk of DCM for individuals with 8 risk alleles compared to individuals with 5 risk alleles (median of the referral population). In silico annotation and functional 4C-sequencing analyses on iPSC-derived cardiomyocytes identify SLC6A6 as the most likely DCM gene at the 3p25.1 locus. This gene encodes a taurine transporter whose involvement in myocardial dysfunction and DCM is supported by numerous observations in humans and animals. At the 22q11.23 locus, in silico and data mining annotations, and to a lesser extent functional analysis, strongly suggest SMARCB1 as the candidate culprit gene. Conclusion : This study provides a better understanding of the genetic architecture of DCM and sheds light on novel biological pathways underlying heart failure. Graphical Abstract: